Production of Liquid Organic Fertilizer from Rice Wash Water and Its Use in Cultivating Curly Lettuce (Lactuca sativa L.) to Support SDG 2 in Kampoeng Pintar Oase Surabaya - Prihatinningtyas, Tri Meiriana; Fitrihidajati, Herlina; Candra, Adi; Cholis, Nur; Aseyan, Aseyan (Journal of Community Service and Empowerment, 2026)
High consumption of rice in Indonesia produces rice washing water waste, which provides an incentive to utilize rice washing water waste into Liquid Organic Fertilizer (LOF). Research at Kampoeng Pintar Oase aims to describe the quality of Rice Washing Water Waste (RWWW) LOF, the effective concentration of RWWW LOF application on plant height, number of leaves, weight and morphology of curly lettuce, and the role of RWWW LOF in curly lettuce cultivation to support SDG 2. The research was analyzed descriptively quantitatively. The research went through two stages, production of LOF through observation with parameters of N, P, K, Fe, organic C, and C/N ratio, and the implementation of LOF on curly lettuce plants through experimentation conduted with four treatments (P0: control, P1: 25%, P2: 50%, P3: 75%) and three repetition. Nutrient testing was carried at the BSPJI Laboratory. Quality test results showed that the nutrient content of LOF was low compared to the Ministry of Agriculture's standard quality No. 261 of 2019. Despite the low nutrient content, LOF implementation affected curly lettuce growth, as observed through plant height, number of leaves, wet weight, and the morphology. The most effective concentration was P3 (75%), which yielded the best results with an average height of 17.6 cm, 9 leaves, and a fresh weight of 33 gram. Beyond biological growth, utilizing RWWW LOF provides substantial economic benefits by reducing cultivation costs. This circular economy model promotes community level zero waste practices and directly contributes to sustainable agricultural targets under SDG 2.